Examining the Impact of Communication on Employee Performance and Job Satisfaction: Unraveling the Dynamics of Workplace Interaction and Its Effects on Organizational Success - Sadikin, Mochamad Rizki; Junaedi, Junaedi; Zahra, Annisa (Mahesa Research Center, 2024)
This research is focused on PT. XYZ, a company involved in the printing and production of flexible packaging. As a result, the findings may not be fully applicable to other organizations or industries, as they are specific to the unique context of this company. The study utilized a sample size of 45 employees, which, while adequate for the scope of this research, is relatively small and may not capture the full range of experiences and perceptions present in larger or different organizational environments. The analysis employed Structural Equation Modeling (SEM) with Partial Least Squares (PLS) methodology, which can be sensitive to both sample size and data distribution. Therefore, future research could improve upon this study by using a larger and more diverse sample, which would allow for a broader understanding of the relationship between communication, job satisfaction, and employee performance. Additionally, adopting a longitudinal approach could provide insights into how these factors evolve over time and in different contexts, offering a deeper understanding of the dynamics at play in diverse organizational settings.